2021
DOI: 10.1186/s13048-021-00823-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel CNV-related prognostic signature predicting prognosis in patients with breast cancer

Abstract: Background Copy number variation (CNVs) is a key factor in breast cancer development. This study determined prognostic molecular characteristics to predict breast cancer through performing a comprehensive analysis of copy number and gene expression data. Methods Breast cancer expression profiles, CNV and complete information from The Cancer Genome Atlas (TCGA) dataset were collected. Gene Expression Omnibus (GEO) chip data sets (GSE20685 and GSE314… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Hu et al developed a model to predict the prognosis of breast cancer patients based on CNV-related genes. The area of the ROC curve for this model was 0.7, 0.63, and 0.58 in the TCGA test set, while the AUC values were 0.66,0.68, and 0.71 in the TCGA all data sets 14 . In this study, we constructed a risk model based on aneuploidy-associated genes with AUC values of 0.7, 0.81, and 0.77 in the GEO cohort, respectively.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hu et al developed a model to predict the prognosis of breast cancer patients based on CNV-related genes. The area of the ROC curve for this model was 0.7, 0.63, and 0.58 in the TCGA test set, while the AUC values were 0.66,0.68, and 0.71 in the TCGA all data sets 14 . In this study, we constructed a risk model based on aneuploidy-associated genes with AUC values of 0.7, 0.81, and 0.77 in the GEO cohort, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that in cancer cells, chromosomal aneuploidy can lead to copy number alterations 13 . Hu et al 14 identified a total of nine genes to be able to independently predict the prognosis of breast cancer patients based on public databases of breast cancer and CNV data. Bian et al 15 comprehensively analyzed CNV differential data and differentially expressed gene data from TCGA and screened eight CNV driver genes (including AKR1B15 , TRIM16L , CBX2 , CDCA8 , EZH2 , FLVCR1 , EPS8L3 , and GPRIN1 ) to generate a prognostic model that could well predict the prognosis of patients with hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…With our knowledge, all the above five necroptosis-related biomarkers are protein-coding genes and are the first to be assigned significance as diagnostic markers for CHD. By reviewing the available literature, it was found that increased FAM166B expression relates to a favorable prognosis in breast cancer (BRCA) and is likely to be an independent prognostic factor [ 48 ]. Besides, this gene was shown to be significantly upregulated (3.693-fold) in multiple symmetric lipomatosis (MSL) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…CNV burden in all chromosomes of NAC-sensitive patients was fewer than that of NAC-resistant patients before NAC treatment. Since the CNVs are considered a key factor in the genetic variation of tumors (Hu et al, 2021), it seems that less CNV burden indicated better response in treating patients (Walker et al, 2017). CNVs were also discovered in a variety of genes following chemotherapy, notably in genes that control drug absorption into cells and drug metabolism (Willyard, 2015).…”
Section: Discussionmentioning
confidence: 99%